2022
DOI: 10.37801/ajad2022.19.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions on the Challenges of Banana Cultivation and Bio-based Technology Use Among Malaysian Smallholder Farmers

Abstract: Bananas are one of the most commonly grown fruit crops in Malaysia, but local production has declined in recent years. Through site visits and interviews with 74 smallholder banana farmers, this study sought to know the current situation of the local smallholder banana industry, the challenges faced in commercial banana cultivation, and the use of bio-based technologies to address the challenges. The farmers cited increasing production costs, pests and diseases, and yield uncertainties as major challenges to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Next, four articles were published in 2020 [34][35][36][37] and three articles from 2018 [38][39][40] . Two articles were published in 2017 [41,42] , 2019 [43,44] and 2022 [45,46] . Figure 2 shows the states where the studies were conducted.…”
Section: General Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, four articles were published in 2020 [34][35][36][37] and three articles from 2018 [38][39][40] . Two articles were published in 2017 [41,42] , 2019 [43,44] and 2022 [45,46] . Figure 2 shows the states where the studies were conducted.…”
Section: General Resultsmentioning
confidence: 99%
“…On the other hand, there are state with no article published that derived data from it. It cannot be concluded that this state does not have any smallholder plantation farmers, Perak (1) [24] Selangor (2) [35,46] Pahang (2) [28,34] Johor (2) [30,41] Sarawak (6) [25,32,37,[42][43][44] Sabah (5) [27,36,[38][39][40] Peninsular Malaysia (1) [24] Malaysia (4) [29,31,33,45] Acknowledgement of challenges faced by oil palm smallholders farmers in Sarawak Mohd Shafiai et al [36] Kesan sikap, faktor halangan dan manfaat tanggapan pekebun kecil sawit persendirian kepada niat menggunakan mikro kredit Islam 2020 Islamiyyat Acknowledgement of challenges faced by oil palm smallholders farmers in Perak Manaf et al [39] Mendepani kekangan inovasi dan teknologi dalam kalangan pekebun kecil sawit di Sabah 2018…”
Section: General Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These images are then analysed to determine the distribution and density of crops throughout the field. This method allows farmers to efficiently monitor crop health, identify areas of overgrowth or undergrowth, and make informed decisions regarding irrigation, fertilization, and pest management [15][16][17][18].…”
Section: Drones As Alarmmentioning
confidence: 99%